HORMONAL BACKGROUND OF THE FETOPLACENTAL COMPLEX AND PSYCHOEMOTIONAL STATE IN PREGNANT WOMEN LIVING IN THE REGION OF MILITARY CONFLICT - Былым, Галина Васильевна; Носкова, Оксана Владимировна; Литвинова, Елена Валерьевна (Mother and Baby in Kuzbass, 2024)
The purpose of the study – to study the hormonal background of the fetoplacental complex and the psycho-emotional state in pregnant women living in the region of military conflict.Material and methods. 85 pregnant women aged 27 to 32 were examined. The main group included 55 women examined in 2020-2023. The control group consisted of 30 healthy pregnant women examined in peacetime. The study of hormones of the fetoplacental complex and the psychoemotional state was conducted in the I, II, III trimesters of pregnancy and on the 3-4 day of the postpartum period.Results. In the first trimester of pregnancy in the main group 2 (3.6 %) patients were in a state of psychoemotional stability, 8 (14.5 %) pregnant women (p < 0.05) were in a state of psychoemotional tension (p < 0.05), 21 (38.2 %) patients (p < 0.05) were in a moderate degree, and 24 (43.6 %) women (p < 0.05). In the second trimester, respectively – 3 (5,5 %), 9 (16,3 %), 20 (36,4 %) and 23 (41.8 %) pregnant women (p < 0.05). In the third trimester, respectively – 3 (5,5 %), 13 (23,6 %,) 22 (40,0 %) and 17 (30.9 %) patients (p < 0.05). In the postpartum period 2 (3.6 %) maternity hospitals were in a state of psychoemotional stability, 17 (30.9 %) were in a state of mild psychoemotional stress, 23 (41.8 %) were in a moderate degree, 13 (23.6 %) were in a severe degree (p < 0.05). Against this background, pregnant women of the main group in the second trimester had an increase in the concentration of placental lactogen by almost 20.0 %, estradiol and cortisol by almost 50.0 % compared with the control parameters (p < 0.05). In the third trimester of pregnancy in the main group, placental lactogen decreased by 20.0 %, estradiol and cortisol by almost 50.0 % compared with the corresponding indicators in the control group (p < 0.05).Conclusion. The resulting psychoemotional stress of medium and high degree in pregnant women living in a military conflict zone has an adverse effect on the hormonal background of the fetoplacental complex and indicates both tension and a violation of the compensatory capabilities of the fetoplacental system. The research obtained indicates the need to develop and apply therapeutic and preventive measures with the inclusion of rational methods of psychocorrection for pregnant women and maternity patients living in a military conflict zone.
Keywords: pregnancy; military conflict; psychoemotional state; psychoemotional tension; hormonal background of the fetoplacental complex